IMPLEMENTASI KEBIJAKAN PEMANFAATAN ALOKASI DANA DESA - Virgie Delawillia Kharisma; Anwar '; Supranoto ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2013)
This study aims to determinethe allocation of policy implementation in the Village Fund Pasongsongan Village, DistrictPasongsongan, Sumenep fiscal year 2008-2012. The method used was a longitudinal descriptivequalitative approach. Data retrieval techniques using the documentation, interviews, observation,and triangulation. Determination of informants with purposive sampling techniques and snowballsampling. The process of data analysis to study the content and Model Miles and Huberman. Policyof 70% utilization of funds ADD in the budget last five years focused on physical develop-ment,namely infrastructure development for rural government and transportation infrastructure development.While five other areas of community development activities that more directly touches the welfare ofthe people neglected to include the development of production, marketing, appropriate technology,health and education by reason of lack ADD goverment received..Key words: decentralization, policy implementation, allocation of village funds, community empowerment.